The Utilization of Semantic Mapping to Teach Vocabulary at SMP Tri Dharma Palembang - Maulidia, Affifa; Nike Angraini, (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study investigated the effectiveness of semantic mapping in enriching students’ vocabulary mastery. Using a quantitative approach, the research involved 29 eighth-grade students from Tri Dharma Junior High School Palembang in the 2023/2024 academic year. A one-group pretest-posttest design was employed, with data collected through multiple-choice tests and questionnaires. Over twelve meetings, including a pretest, nine treatments, and a posttest, results showed significant vocabulary enrichment. The Wilcoxon signed-rank test revealed a Z value of -3.885 and a p-value below 0.001, confirming the enrichment's statistical significance. The study concluded that semantic mapping effectively improvement vocabulary mastery and motivated students to learn further.